2021
DOI: 10.2147/dddt.s334325
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of Anti-Hyperglycemic Agents and Traditional Chinese Medicine on Gut Microbiota in Type 2 Diabetes

Abstract: Type 2 diabetes mellitus (T2DM) is a widespread metabolic disease characterized by chronic hyperglycemia. Human microbiota, which is regarded as a "hidden organ", plays an important role in the initiation and development of T2DM. In addition, antihyperglycemic agents and traditional Chinese medicine may affect the composition of gut microbiota and consequently improve glucose metabolism. However, the relationship between gut microbiota, T2DM and anti-hyperglycemic agents or traditional Chinese medicine is poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“… 14 Interestingly, intestinal barrier injury is independently driven by hyperglycemia, 15 and our previous study has further confirmed the relationship between intestinal barrier injury and hyperglycemia in humans. 16 In addition to the negative effects of hyperglycemia on the intestinal barrier and sepsis, some anti-hyperglycemic agents have been proven to protect against intestinal barrier injury 17 and alleviate sepsis-induced organ dysfunction in numerous animal experiments. 18 …”
Section: Introductionmentioning
confidence: 99%
“… 14 Interestingly, intestinal barrier injury is independently driven by hyperglycemia, 15 and our previous study has further confirmed the relationship between intestinal barrier injury and hyperglycemia in humans. 16 In addition to the negative effects of hyperglycemia on the intestinal barrier and sepsis, some anti-hyperglycemic agents have been proven to protect against intestinal barrier injury 17 and alleviate sepsis-induced organ dysfunction in numerous animal experiments. 18 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of metagenomic studies, there has been a growing awareness of the important role of the gastrointestinal microbiome in public health and diseases, including digestive system diseases such as in ammatory bowel disease [28], colorectal cancer [29], irritable bowel symptoms [30], and parenteral diseases such as diabetes [31,32], coronary heart disease [33,34], and Alzheimer's disease [35,36]. An imbalance of the gastrointestinal microbiome occurs early in the development of SAP.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid has antibacterial activity [ 61 ], and a compressed mixture of insulin and palmitic acid can sustain a reduction in hyperglycemia in rodents [ 62 ]. Additionally, research shows that deoxycholic acid-triazole conjugates have good inhibitory effects against B. subtilis [ 63 ]; deoxycholic acid is involved in improving glucose metabolism to ameliorate hyperglycemia [ 64 ]. In short, we have found 6 possible components of corn silk with antibacterial and hyperglycemia activities.…”
Section: Discussionmentioning
confidence: 99%